ANALISIS KENYAMANAN DI TEMPAT KERJA BAGI GENERASI Z DALAM BEKERJA DI ERA GLOBALISASI - Muhammad Rizki Dwi Saputra; Septiani Septiani (LPPM Institut Pendidikan Nusantara Global, 2022)
The workplace is the second home after our original residence where we must have comfort at work. In this era of globalization, there are lots of generation Z who are uncomfortable at work because the environment is one of the main factors where generation Z is uncomfortable at work. This study attempted to examine using descriptive qualitative techniques and data collection using interview techniques. Data analysis is carried out interactively and continues continuously until complete, so that the data is saturated. Activities in data analysis are: Data Reduction (Data Editor). Data Dispay (Data Presentation), Conclusion Drawing/ Verification. This research was conducted at PT. Gunung Salak Sukabumi located in Babakan Pari, Kec. Cidahu, Sukabumi Regency, West Java Based on the results of the study it was explained that only 50% of Generation Z are comfortable at work. Some or another 50% feel uncomfortable at work. The conclusion obtained in this study is that a sense of comfort at work will bring good factors into the sensory nerves and also the psychology of its employees and raise the spirit of performance in a company. For this reason, this convenience is very important, especially in the era of globalization where humans are increasingly doing bad things and there is envy and mutual envy and bringing each other down.